2012
DOI: 10.3892/ijmm.2012.1134
|View full text |Cite
|
Sign up to set email alerts
|

Hexane extract from Uncaria sinensis exhibits anti-apoptotic properties against glutamate-induced neurotoxicity in primary cultured cortical neurons

Abstract: We explored the neuroprotective effects of a hexane extract from Uncaria sinensis (HEUS) against glutamate-induced toxicity focusing on its anti-apoptotic mechanism in primary cultured cortical neurons. Pretreatment with HEUS resulted in significantly reduced glutamate-induced toxicity in a dose-dependent manner with a decrease in the release of lactate dehydrogenase. Morphological assay and flow cytometry were performed for determination of the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Pretreatment with 1-methoxyoctadecan-1-ol resulted in concentration-dependent inhibition of glutamate-induced toxicity (Fig. 2) and prevention more specifically at a very lower dose, compared with our previous studies [6]. Exposure to excitotoxic levels of glutamate induces two distinct types of programmed cell death, sharing both necrosis and apoptosis [19].…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Pretreatment with 1-methoxyoctadecan-1-ol resulted in concentration-dependent inhibition of glutamate-induced toxicity (Fig. 2) and prevention more specifically at a very lower dose, compared with our previous studies [6]. Exposure to excitotoxic levels of glutamate induces two distinct types of programmed cell death, sharing both necrosis and apoptosis [19].…”
Section: Discussionsupporting
confidence: 49%
“…p38 MAPK plays an integral role in caspase activation and mitochondrial dysfunction by Bcl-2 family [38], [39] and blocking via the PI3K/Akt signaling pathway with downstream effector Bcl-2 [40], [41]. Our previous results showing that hexane extract from U. sinensis enhanced Bcl-2 expression with alleviation of caspase activation [6] may suggest possible involvement of another pathway. However, Western blot analysis showed that co-treatment resulted in complete blockade of all activated calpain, STEP cleavage, and p38 phosphorylation, in which methoxyoctadecan-1-ol exerted neuroprotective effects similar to those of calpeptin.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…One way to reduce glutamate toxicity is to use antioxidant compounds such as medicinal plants. Recent studies have shown some herbal medicines have protective effects against glutamate such as peel and seed extract of Citrus aurantium [16], Persea major [8], Uncaria sinensis [20], Scrophularia striata Boiss [36], and Withania somnifera [22]. In this research, we used Ferula gummosa extract against glutamate toxicity in two cell lines: PC12 and N2a.…”
Section: Discussionmentioning
confidence: 99%